(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The global discourse on heritable genome editing is dominated by Western perspectives. A broadening of this discourse is advocated. A South African perspective on heritable genome editing is provided, focusing on differences in culture and context, which illustrates the need for a governance approach to heritable genome editing that is distinctly less restrictive. This, it is argued, is because categorical claims about the morality of heritable genome editing that are routinely expressed as worthy of being aspects of the global governance framework lack a recognition of differences in culture and context between different countries, and hence constitute ethical imperialism.